A RETROSPECTIVE STUDY OF CYBERBULLYING ON SOCIAL NETWORKING - Apriyanto, S; Dalman,; Dalman,; Anum, A (International Journal of Psychosocial Rehabilitation, 2020)
Cyber Era creates internet technology and presents a new phenomenon in the media which has become a new media called social networking. The reputation of online social networks has created a wide range of public communication among users, and this leads to an enormous extent of information generated by users. Over the past few years, cyberbullying has become a major problem for the advance of online communication and social networking. Internet bullying is known as a grave national wellbeing problem among online social network users. This paper focuses on finding the risks of cyberbullying and raising awareness about cyberbullying prevention. The researcher uses secondary sources such as books, magazines, electronic sources, papers, and newspapers. Primary sources, such as interviews and field studies, cannot be done, which the researcher cannot access due to lack of time. Finally, social networks like sharp knives with proper usage, options, and responsibilities, many social networking sites are useful. But if used without responsibility, social media may have a negative impact.